2016
DOI: 10.1021/acschembio.5b00897
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the 3-O-Sulfate Proteome—Enhanced Binding of Neuropilin-1 to 3-O-Sulfated Heparan Sulfate Modulates Its Activity

Abstract: Binding of proteins to heparan sulfate is driven predominantly by electrostatic interactions between positively charged amino acid residues in the protein and negatively charged sulfate groups located at various positions along the polysaccharide chain. Although many heparin/heparan-sulfate-binding proteins have been described, few exhibit preferential binding for heparan sulfates containing relatively rare 3-O-sulfated glucosamine residues. To expand the “3-O-sulfate proteome,” affinity matrices were created … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 66 publications
(80 citation statements)
references
References 46 publications
2
69
0
Order By: Relevance
“…Previous studies reported that HSPG might act as a co‐receptor to enhance many cancer hallmark pathways by stabilizing ligand‐receptor complexes in carcinoma . However, different lengths and variable sulfation of HS lead to structural heterogeneity, which may result in conflicting functional effects . Indeed, diverse structures of HS with different lengths and modifications have distinct binding affinities for growth factors and cytokines .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that HSPG might act as a co‐receptor to enhance many cancer hallmark pathways by stabilizing ligand‐receptor complexes in carcinoma . However, different lengths and variable sulfation of HS lead to structural heterogeneity, which may result in conflicting functional effects . Indeed, diverse structures of HS with different lengths and modifications have distinct binding affinities for growth factors and cytokines .…”
Section: Discussionmentioning
confidence: 99%
“…36 The abundant negatively-charged HS/CS chains of endothelial-cell-surface proteoglycans bind VEGF-A165a and, as with HS/CS chains in the extracellular matrix, can differentially regulate accessibility/storage of this isoform (and other isoforms with a heparin-binding domain, with affinities depending on the exon 6–8 combinations 37 and tertiary fold). These HS/CS chains can also modify the ability of VEGF isoforms to bind to VEGFR2 and NRPs, which themselves interact with and colocalize with cell surface HSPGs (VEGFR2 was shown to directly interact with HS chains on HSPGs expressed in endothelial cells via a stretch of residues between D6-D7 of VEGFR2 38-41 ; heparin also binds to VEGFR1 42-44 , NRP1 17 and NRP2 45 independent of VEGFs).…”
Section: Evidence For Modulation Of Vegf and Nrps By Hspgsmentioning
confidence: 99%
“…38 Additionally NRP1-specific GAG modification of HS/CS chain on Serine 612 30 can enhance VEGF-A165a binding to the NRP core protein, which may play a role in the VEGF-A165a-responsiveness of endothelial cells.…”
Section: Evidence For Modulation Of Vegf and Nrps By Hspgsmentioning
confidence: 99%
“…Recent work has shown that the function of 3- O -sulfation catalyzed by HS3ST2 depends on gene dosage, suggesting that 3- O -sulfation and 3- O -sulfate dependent activities may be generally regulated at the level of sulfotransferase expression (Thacker et al, 2016). Thacker and colleagues showed that neuropilin-1 binds to 3- O sulfated HS with high affinity and that genetic reduction of 3- O -sulfation desensitized neuropilin-1 to semaphorin3A induced growth cone collapse in dorsal root ganglion explants (Thacker et al, 2016). Interestingly, gene polymorphisms in neuropilin-2 have been associated with autism in Chinese Han population (Wu et al, 2007).…”
Section: Heparan Sulfate and Heparan Sulfate Proteoglycansmentioning
confidence: 99%